Screening for congenital disorders of glycosylation in the first weeks of life - Thiel, Christian; Meßner-Schmitt, Dorothea; Hoffmann, Georg F.; Körner, Christian (Journal of inherited metabolic disease, 2013)
Inherited monogenetic human disorders due to deficiencies in the complex metabolic pathways for N- and O-glycosylation of glycoconjugates are termed ‘congenital disorders of glycosylation’ (CDG). Since the number of these defects with mostly severe multisystemic phenotypes has been rapidly expanding in recent years, the interest of paediatricians has also increased resulting in a rising amount of patient samples with the suspicion of CDG. In general, primary diagnostics for CDG start with investigations on the glycosylation state of serum transferrin, the ‘gold standard’ in the field for many years. However, the use of transferrin shows an analytical problem in the time span from birth up to the 3rd month of life. In this developmental period oligosaccharide moieties N-linked to proteins are often incomplete, resembling a CDG pattern and leading to false-positive results. It is therefore necessary to establish a reliable and fast diagnostic procedure for this span of life. Here we show that the glycosylation state of serum α-1-antitrypsin is already fully existent shortly after birth allowing an alternative diagnostic approach for the investigation of CDG in the first weeks of life. The method can easily be established in every laboratory especially with previous experience in transferrin analysis.
Published online: 19 September 2012
Gesehen am 03.02.2022